Substituição do milho pela glicerina em suplementos múltiplos para novilhos Nelore em pastejo - Silva-Marques, Renata Pereira da; Zervoudakis, Joanis Tilemahos; Hatamoto-Zervoudakis, Luciana Keiko; Cabral, Luciano da Silva; Alexandrino, Emerson; Neto, Antonio Jose [UNESP]; Werner Koscheck, Jefferson Fabiano [UNESP]; Rondena Pesqueira Silva, Lilian Chambo [UNESP]; Goncalves da Silva, Rafael Ferrato (Univ Estadual Londrina, 2015)
The objective was to evaluate the performance and production costs of Nellore steers growing on Brachiaria brizantha cv. Marandu during the dry season receiving mineral supplements with partial replacement of corn by residual glycerin. 40 Nellore steers with initial body weight of 203.12 +/- 20.10 kg and average initial age of 12 months, distributed into eight paddocks of 1.6 ha each, were used. The experimental design was completely randomized with five replicates and eight supplements. Supplements with levels of partial replacement of corn by glycerin were evaluated: 0% (G0), 10% (G10), 20% (G20), 30% (G30), 40% (G40), 50% (G50) and 60% (G60) provided on the amount of 1 kg/animal/day in the natural matter, and a mineral supplement (MS). The average daily gain (ADG) was higher (P<0.05) in animals receiving supplements G30 (0.609 kg), G40 (0.588 kg) and G60 (0.611 kg) in relation to supplements G0 (0.546 kg), G10 (0.509 kg), G50 (0.561 kg) and MS (0.223 kg). There were differences (P <0.10) in ADG in supplemented animals when compared to MS. The supplemented animals showed higher ADG (P<0.05) compared to MS. The different levels provided positive financial return. It is concluded that the supply of multiple supplements replacing the corn by glycerol in production systems of steers in the dry period provides higher productive performance levels of 30, 40 and 60% and positive financial return to levels of 60% of replacement, demonstrating thus, its potential use for intensive systems of beef production on pasture.

Objetivou-se avaliar o desempenho produtivo e os custos de produção de novilhos Nelore recriados em pastagem de Brachiaria brizantha cv. Marandu durante o período seco do ano recebendo suplemento mineral e suplementos com substituição parcial do milho por glicerina residual bruta. Foram utilizados 40 novilhos Nelore com peso corporal médio inicial de 203,12 ± 20,10 kg e idade média inicial de 12 meses, distribuídos em oito piquetes de 1,6 ha cada. O delineamento foi inteiramente casualizado com oito suplementos e cinco repetições. Foram avaliados suplementos com níveis de substituição parcial do milho por glicerina: 0% (G0); 10% (G10); 20% (G20); 30% (G30); 40% (G40); 50% (G50) e 60% (G60), fornecidos na quantidade de 1 kg/animal/dia na matéria natural, além de um suplemento mineral ad libitum (SM). O ganho médio diário (GMD) foi maior (P<0,05) em animais recebendo os suplementos G30 (0,609 kg), G 40 (0,588 kg) e G60 (0,611 kg) em relação aos suplementos G0 (0,546 kg), G10 (0,509 kg), G50 (0,561 kg) e SM (0,223 kg). Os animais suplementados apresentaram maior GMD (P<0,05) em relação ao SM. Os diferentes níveis proporcionaram retorno financeiro positivo. Concluise, que o fornecimento de suplementos múltiplos substituindo o milho por glicerina em sistemas de produção de novilhos de corte no período da seca proporciona maior desempenho produtivo nos níveis de 30, 40 e 60% e retorno financeiro positivo até níveis de 60% de substituição, demonstrando, portanto, o seu potencial de uso em sistemas intensivos de produção de carne bovina a pasto.
Replacement of corn by glycerin in multiple supplements for Nellore steers on pasture
Keywords: Beef cattle; Production cost; Growing; Supplementation; Bovinos de corte; Custo de produção; Recria; Suplementação